Analisis Pengelolaan Keuangan Desa Berdasarkan Permendagri No. 20 Tahun 2018 Dalam Upaya Optimalisasi Dana Desa (Studi Kasus Pada Desa Pantis Kecamatan Pahae Julu Kabupaten Tapanuli Utara) - Desi Katriana Panjaitan; Mustapa Khamal Rokan; Laylan Syafina (LPPM Universitas Labuhanbatu, 2023)
This study analyzes village financial management with laws and regulations that regulate it. This research was conducted in Pantis Village, Pahae Julu District, North Tapanuli Regency. This study aims to determine and analyze the suitability of village financial management and the principles of financial management in Pantis Village, Pahae Julu District, North Tapanuli Regency with Permendagri no. 20 of 2018. This type of research is a case study with a qualitative descriptive analysis approach. Data is generated by distributing questionnaires, interviews, and documentation. The object of this research is village financial management in Pantis Village. The results of this study indicate that the financial management of Pantis village, starting from planning to village financial accountability and the principles of village financial management in Pantis Village, are in accordance with Permendagri no. 20 of 2018, but from the results of the questionnaire that researchers have distributed, there are still some people who are still dissatisfied, especially with the performance of village officials who are considered to be less transparent in managing village finances. To overcome these problems, village leaders and officials should be more transparent and more open about managing village finances.